OCCURRENCE, DAMAGE PATTERN AND STATUS OF THE RICE LEAF FOLDER CNAPHALOCROCIS RURALIS WALKER (LEPIDOPTERA: CRAMBIDAE) IN ERIANTHUS SPP. IN INDIA. (2nd April 2018) - MAHESH, P.; SRIKANTH, J.; CHANDRAN, K.; SINGARAVELU, B.; SALIN, K. P.; JAYABOSE, C.; BALAN, S.
SUMMARY: We investigated the occurrence and status of the leaf folder Cnaphalocrocis ruralis (Walker) (Lepidoptera: Crambidae) in accessions of Erianthus spp. maintained as a part of the world germplasm collection at the Research Center of ICAR-Sugarcane Breeding Institute, Kannur, Kerala State, India. The nature, pattern, extent and year-to-year variation in damage were examined and accessions categorized based on relative incidence. The larvae of C. ruralis caused characteristic injury by feeding on chlorophyll bearing tissues leading to the formation of white and transparent streaks on the leaf blade. The grown-up larvae folded the leaf longitudinally with the adaxial surface inside the fold and exposing the abaxial surface, the edges being held in place by bands of silk thread at regular intervals. The length of leaf folds varied from 2.6 to 27.0 cm with a mean of 9.1 cm, which roughly constituted 7.3% of the mean length of the leaf blade. Leaf length, leaf width and leaf area were not correlated with either the leaf fold length or the number of webs. However, the leaf fold length was positively correlated with the number of webs. Attack rates (infestation rate) on cane basis (up to 69.0%) were generally higher than the damage rates (intensity) on leaf basis (up to 50.0%); infestation index ranged between 0.0 and 13.7%. Correlations between infestation rate and intensity varied among the three study years. Non-parametric analysis indicated significant differences among the three years for percent of infested canes and infestation index but not percent of damaged leaves. All accessions showed C. ruralis incidence in at least one experimental year, indicating that none of the accessions tested was immune to its attack. When all 74 accessions were considered on the basis of infestation index, 85.1% were placed in low and moderate categories and only 14.9% in high incidence category. Within the accessions of Erianthus spp., leaf area was not related to infestation rate of cane or damage rate of leaves but positively related to infestation index. The dynamics of the leaf folder in the predominantly paddy ecosystem were discussed in the light of its first occurrence in Erianthus spp. accessions in India and the world.